Método General para la Detección de Imágenes Alteradas Utilizando Técnicas de Compresión - Roman Gonzalez y Colls., Avid (2018)
Currently, with the excessive increase in the amount of digital information, whether text, audio, video or images and the acceleration of technology, it is very easy to make some alterations in this type of data that can be visible or not. These alterations may have different objectives, such as introducing a watermark to protect the copyright, or to enter a hidden message to be sent in secret, also alterations to add or remove any information for alter the original information for any purpose, whether good or bad. Faced with all these different possibilities of alterations that often cannot be detected by a simple visual examination; that is why it is necessary to develop and implement automated methods that allow us to identify when a data is altered. In this paper we focus only on the detection of altered or manipulated images.